Identifying Endometrial Delay Improves Treatment Outcome in Women with Thin Endometrium and Infertility - Namshir, Narangerel; Darmaa, Yanjinsuren; Davaatseren, Munkhtsetseg; Choi, Bum Chae (Central Asian Journal of Medical Sciences, 2024)
Objective: To determine the impact of endometrial delay on reproductive outcomes. Method: We enrolled 62 infertility women with thin endometrium pre- and post-study in 2020-2023. Infertile women with an endometrial thickness of <7 mm were included and followed in the study. All participants had endometrial delay determined and adjusted before initial Assisted reproductive technologies (ART). After, infertility treatment was started. ART outcomes were evaluated by endometrial thickness and implantation rate. Endometrial thickness was compared to pre-hormone replacement treatment at 48 and 72 hours post-hormone therapy. Results: The study included 62 women aged 26-45 who were diagnosed with infertility and thin endometrium. Endometrial thickness was sufficiently increased before and after treatment for all participants. Histological analysis diagnosed endometrial delay (not appropriate WOI) in 73.6% of all women. After adjusting the WOI in study participants, there was a statistically significant increase in endometrial thickness post-hormone replacement therapy. The study participants were women who had failed at least one implantation, and the implantation rate after WOI adjustment was 58.5%. Conclusions: In 70% of infertility women, endometrial is delayed. In women with thin endometrium, the precise determination of WOI increases ART treatment outcomes.